Assistance of Agroforestry Programs in Bojonegoro Regency - Firdausi, Rizal Zubad; Pratiknyo, Y.B (IDFoS Indonesia, 2021)
The purpose of the assistance program was to improve community welfare through replicating the successful implementation of previous programs in improving the livelihoods of rural communities around the JTB project operation area to other villages; improving environmental sustainability, especially forest sustainability in an effort to contribute to reducing carbon emissions in Bojonegoro Regency; realizing the principle of equity and justice in the implementation of community development programs that are not limited to the project area but also communities outside the project area in accordance with regional policy priorities, and maintain good relations with the surrounding community and local government so that businesses is able to run smoothly. The Participatory Action Research (PAR) method was used in this assistance program. The results of the assistance were the establishment of good relations from various parties, including KPH Bojonegoro, Bapedda, DLH, PEPC and IDFoS Indonesia through forest conservation activities, there had been an increase in the knowledge and capacity of forest farmers and the existence of agroforestry businesses in forest areas, the planting of 1500 longan trees and 30 durian trees as well as providing business operational assistance such as production and operational facilities, with longan cultivation farming, it was estimated that in the next 2 years at harvest, farmers were able to harvest as much as 3,000 kg with a turnover of Rp. 60,000,000 approximately in one harvest cycle, and the results of the evaluation mandate that there was 3 months of surveillance to minimize crop loss, and had been carried out by LMDH and Perhutani. To deal with the upcoming drought, it was necessary to prepare effective and possible watering because the location was in the middle of the forest with limited transportation access.